Modeling and Simulation of Biomass Gasification with Aspen Plus for Different Types of Local Biomass from Riau Province - Asshiyami Zikra; Ricky Okta Yohannes; Faiprianda Assyari Rahmatullah; Hari Rionaldo; Zulfansyah (CHEESA: Chemical Engineering Research Articles, 2025)
Gasification is a promising technology for electrical energy generation systems in palm oil mills. The syngas components, namely CH4, H2, and CO, produced from gasification can be used as fuel to produce steam, which will be applied in turbine generators to produce electricity. Therefore, this study aimed to simulate and validate a flowsheet model of gasification process for oil palm mill waste using Aspen Plus to achieve an optimal syngas composition, and conduct sensitivity analysis by varying gasification temperature, equivalent ratio, as well as correlating biomass moisture content to syngas composition. Biomass moisture content, equivalent ratio, and gasification temperature are important parameters that affect the chemical composition and heating value of syngas analyzed using the sensitivity analysis method. The results showed that the syngas composition was sensitive to the parameters of temperature, moisture content, and equivalent ratio. The operating conditions of gasification process to obtain a high heating value of syngas include 650?C gasification temperature, 0% moisture content, and 0.2 equivalent ratios.